Model Sinergitas Antar Lembaga Dalam Pengelolaan Zakat Bagi Mustahiq Pedagang Kaki Lima (PKL) - Novriansyah, Yudhi; Supriyati, Supriyati; Darham, Darham (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
In the business world, we are known as Street Vendors (PKL). Street vendors, of course, need capital, but working capital funds are very limited, so there is a possibility of borrowing funds using a payment system that contains usury or better known as loan sharks. In relation to the above, the term productive zakat emerged so that it can provide long-term impact and beneficial value to the zakat mustahiq, including street vendors.). Using qualitative methods with an analytical descriptive approach. The collection technique in this research is literature study, this is done by collecting relevant or appropriate data needed for research. The target of this research is the existence of contemporary Sharia Economic Law and its relevance in Indonesia. The results of the study show a synergistic zakat management model, involving several institutions in empowering mustahiq street vendors. Integrative and collaborative steps of the Adaptation, Goal Attainment, Integration and Latency (AGIL) model. In the corridor of synergy between BAZNAS and the Ministry Of Social Affairs, Ministry Of Trade, Ministry Of Education And Cultural, Ministry Of Cooperative Small Micro anda Medium Enterprise, The Universities and Islamic Youth Organizations which support the synergy of empowering mustahiq street vendors. This model of synergy between institutions in managing zakat can form a mustahiq who can be self-empowered and change his fate out of poverty.